Estimation of Optimal Blasting Geometry Using Multivariate Modeling to Reduce Boulder Potential and Improve Mining Production - Andre Octova; Milia Putri; Dedi Yulhendra (Georest, 2022)
One of the most critical stages in mining operations is rock encroachment. A commonly used method of laying rocks is blasting which aims to cleave rocks according to the size of the planned fragmentation. The effectiveness of a blasting activity is a benchmark for the success of loading and transportation activities which greatly affects the achievement of mining production targets. This study aims to estimate the optimum blasting geometry to minimize the percentage of the number of boulders so that loading activities become more effective and production targets are achieved. The research case study was conducted on 8 blasting blocks in the South Osela Pit located at PT J Resources Bolaang Mongondow, North Sulawesi, Indonesia. The research data consists of detonation fragmentation, digging time, cycle time, digging rate, and ore mining productivity. The research method was carried out by multivariate modeling and estimation of blasting geometry. The results of multivariate modeling show that to achieve the production target of 700 bcm / hour, the percentage of boulders < 4%, digging time 8 seconds, cycle time 14 seconds, and digging rate 800 bcm / hour. The results of the blasting geometry estimation show that to get the percentage of the number of boulders < 4 % then the optimum blasting geometry is a burden of 3.8 meters; spacebar 3.2 meters; stemming 2.2 meters; blast hole depth 5.8 meters, and powder factor 0.42 Kg/bcm.